Experimental investigation on lithium-ion battery thermal management based on flow boiling in mini-channel. (5th May 2017) - An, Zhoujian; Jia, Li; Li, Xuejiao; Ding, Yong
Highlights: A new type of BTM system based on flow boiling in mini-channel are presented. Uniform temperature and volume distribution of battery module are obtained. The temperatures of battery cell are maintained around 40 °C. There exists an appropriate Re number range for boiling heat transfer in mini-channel. Abstract: In order to guarantee the safety and prolong the lifetime of lithium-ion power battery within electric vehicles, thermal management system is essential. A new type of thermal management system based on flow boiling in mini-channel utilizing dielectric hydrofluoroether liquid which boiling point is 34 °C is proposed. The cooling experiments for battery module are carried out at different discharge rates and flow Re number. The cooling effect and the influence of battery cooling on the electrochemical characteristics are concerned. The experimental results show that the thermal management can efficiently reduce maximum temperature of battery module and surface maximum temperature difference. A relatively uniform temperature and voltage distributions are provided within the battery module at higher discharge rate benefit from the advantage of boiling heat transfer with uniform temperature distribution on cold plate. It is shown that the voltage decreases with the increase of Re number of fluid due to the reducing of temperature. There exist slight fluctuations of voltage distribution because of the non-uniformity of temperature distribution within the battery module at higher discharge rates. For different discharge rate, there also exists an appropriate Re number range during which the mode of heat transfer is mainly in boiling heat transfer mode and the cooling result can be greatly improved.